Magnetic nanoparticles of zinc and calcium for magnetic hyperthermia application - Jasso-Terán, Rosario Argentina; Cortés-Hernández, Dora Alicia; Sánchez-Fuentes, Héctor Javier; Reyes-Rodríguez, Pamela Yajaira; León-Prado, Laura Elena (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Cancer is the second cause of death in the world. Magnetic hyperthermia is an alternative treatment which consists of raising the temperature of cancer cells using magnetic nanoparticles. In this work, the synthesis and characterization of two calcium-zinc ferrites (Zn0.50Ca0.50Fe2O4 y Zn0.25Ca0.75Fe2O4) are presented. These ferrites were synthesized by sol-gel method, afterwards they were calcined at 400 °C. The saturation magnetization values were 31.31 and 38.30 emu/g for Zn0.50Ca0.50Fe2O4 (ZCF050) and Zn0.25Ca0.75Fe2O4 (ZCF075, respectively. The average particle size was 14 nm for ZCF050 and 12 nm for ZCF075. Additionally, in vitro bioactivity assessment was performed by immersing samples in simulated body fluid (SBF) for 21 days under physiological conditions of pH and temperature. Only the ZCF075 ferrite showed to be bioactive. The heating capacity of ferrites was evaluated under an appropriate magnetic field using solid state magnetic induction. The working conditions were the following: A magnetic field of 10.4 KA/m and a frequency of 362 KHz. The ZCF050 ferrite reached a temperature of 41.2 °C using a concentration of ferrite/water 20 mg/2ml. The ZCF075 ferrite failed to reach 40 °C. The results obtained in the ferrite ZCF050 indicated that these nanoparticles are potential materials for cancer treatment by magnetic hyperthermia therapy.